Synergistic effect of N-rGO supported Gd doped bismuth ferrite heterojunction on enhanced photocatalytic degradation of rhodamine B - Dixit T.K.; Sharma S.; Sinha A.S.K. (My University, 2025)
An active composite of nitrogen-doped graphene oxide (N-rGO) supported gadolinium doped bismuth ferrite (BGFO), (BGFO/N-rGO), was synthesized by a modified hydrothermal method. The composite was characterized by X-ray photoelectron spectroscopy (XPS), fourier transform-infrared (FT-IR), diffused reflectance spectroscopy (DRS), scanning electron microscope (SEM), energy-dispersive X-ray spectroscopy (EDX), transmission electron spectroscopy (TEM), electrical impedance spectroscopy (EIS), photoluminescence (PL) and mott-schottky (M-S) analysis. Doping of Gd in pristine bismuth ferrite suppressed photoinduced electron-hole pair recombination. This resulted in a significant increase in the photocatalytic activity of BGFO (k = 7.89 gcat-1.h-1) in comparison to bare bismuth ferrite (k = 3.15 gcat-1.h-1) on the degradation of RhB. Further, incorporation of N-rGO with BGFO lead to the formation of a heterojunction that provided high surface area and a passage to transfer the electrons from BGFO to N-rGO. This further reduced the electron-hole pair recombination and improved the photocatalytic degradation of rhodamine B by 600% (k = 18.91 gcat-1.h-1) due to the availability of sufficient charge carriers at the surface of the catalyst. Superoxide ion (O2•) was found most active radical among the various reactive species viz. hydroxyl ion (OH•), electron (e-), and hole (h+) as confirmed by trapping experiments. A proposed mechanism of the degradation process was elucidated by species trapping experiments. © 2020